ECONOMIC ANALYSIS OF DRIED PLUM FRUITS - Monika KABADZHOVA; Martin KOLEV; Nikolay DIMITROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Fruits are beneficial to humans in many ways. They are an essential part of a varied, healthful diet as well as a crucial one. As we know, fruits are seasonal food, and to guarantee longer-term storage and consumption throughout the year, they should be treated differently. The study evaluates economic indicators of three plum cultivars: Stanley, Top Taste, and Top 2000. They were dried using four different methods: in sun, in shade, in dehydrator, in lyophilizer. The study's methodological framework includes: a theoretical overview of plum drying methods, and an analysis of the economic indicators of prune fruits, such as gross production, net income, and profitability rate. The results show that freeze-dried plums have better indicators than the other three drying methods. However, if the freeze-drying method is excluded because the production price is ten times higher than that of sun-dried, shade-dried, and dried-in dehydrator plums, then in that case, the dehydration method shows better economic indicators than the remaining three drying methods at the three cultivars.